دراسة تفريخ الجمبري penaeus وتربيته (Latakia University Journal -Basic Sciences Series, 2018)
تناول البحث دراسة تفريخ وتربية ثلاثة أنواع من الجمبري ذات الأهمية الاقتصادية من ناحية المصايد والاستزراع وهي Penaeus semisulcatus, p japonicus, p.kerathurus وكان الهدف من هذا البحث إنتاج يرقات Juveniles الجمبري من مرحلة فقس البيوض ومرحلة يرقة الناوبليوس Nauplius إلى مرحلة اليرقة البعدية Postlarvae ، حيث يمر الجمبري في سلسلة مراحل يرقية تحتاج إلى أغذية متنوعة. استخدمنا منها الطحلب Nanochloropsis oculata من العوالق النباتية phytoplankton . Brachionus plicatilis من العوالق الحيوانية Zooplankton والقشوي Artemia. وأضيف الغذاء الاصطناعي Artificial diet إلى مرحلة اليرقة البعدية. نفذ هذا البحث في المعهد القومي لعلوم البحار والمصايد – فرع الاسكندرية – اعتباراً من تاريخ 2003-3-23 ولغاية 2003-7-23 . جمعت عينات الجمبري مرتين ، حيث جمع في المرة الأولى P.semisulcatus بتاريخ 2003-5-6 بينما جمع في المرة الثانية النوع p.japonicus والنوع p.kerathurus . درست أثناء انتاج الغذاء الحي وتربية يرقات الجمبري العوامل الفيزيائية والكيميائية اللازمة للنمو والتكاثر        وهي التالية : الحرارة Temperature والملوحة Salinity ودرجة الحموضة (ph) والأوكسجين المنحل Dissolved  oxygen والإضاءة Illumination والتطهير Disinfection : -      أظهرت هذه الدراسة نجاح انتاج الغذاء الحي السابق الذكر. -      بينت هذه الدراسة أن النوع P,semisulcatus يبدأ تكاثره في بداية شهر أيار ، بينما يبدأ النوعان P.japonicus, P.kerathurus .تكاثرهما في بداية شهر حزيران -      أظهرت هذه الدراسة أن تربية يرقات أنواع الجمبري المدروسة في الشروط المخبرية أفضل منها في الظروف الطبيعية خارج المختبر من حيث انخفاض النسبة المئوية لنفوق اليرقات ومن ناحية سرعة تطور اليرقات. بينت هذه الدراسة أن النوع P.kerathurus أفضل للتربية من النوعين السابقين حيث فقست بيوضة بعد مضي           (12) ساعة بينما فقست بيوض النوع P.japonicus بعد مضي (15) ساعة والنوع P.semisulcatus بعد مضي              (18) ساعة. The research deals with the hatching and breeding of three species of Penaeus Prawn, which have a valuable economic importance concerning the fisheries and growing. They are Penaeus Semisulcatus, P.Japonicus, and P. Kerathurus. The aim of this research is to produce the juveniles of Penaeus Prawn from the eggs hatching stage and Nouplius larva stage to the post larva stage where the penaeus prawn passes in a series of larval stages which need various diets and nutrients. we use the following : Nanochloropsis Oculata Algae, from the phytoplankton, Brachionus plicatilus, from the zooplankton, and crustacean Artemia. Thus, the artificial diet has been added to the postlarva stage. This research is done in the national institute of Oceanography and Fisheries sciences, Alexandria Department, from 23/3/2003 till 23/7/2003. The Specimens are collected twice. First; P. semisulcatus only was collected on 6/5/2003, while in the second time, both species of P.Japonicus and P.kerathurus had been collected. Through producing the live food production, and breeding the penaeus prawn Larvae, the physical and chemical parameters which are necessary for growing and reproduction have been studied such as the following : Temperature, Salinity, PH, Dissolved Oxygen, Illumination and Disinfection. This study revealed the success of producing the live food production mentioned previously. This study showed that the species P.semisulcatus begins its reproduction at the beginning of may, whereas both species of P.Kerathurus and P.Japonicus begin their reproduction at the beginning of June. This study revealed that breeding the larvae of Penaeus Prawn species which are studied in the laboratory conditions is better than that in the natural conditions outside of the laboratory due to the decreasing of larvae Mortality percentage and to the rapidity of larvae development. This study has shown that the species P.Kerathurus is better for breeding than the two previous species, eggs hatched after 12 hours while the eggs of the species P.Japonicus hatched after 15 hours, and those of P.semisulcatus after 18 hours. This research has a great economic significance especially becuse some of species of penaeus are bred and live in our regional waters of the eastern basin of the Mediterranean.